Analysis of physical and physiological training demands in women’s basketball - Pau Pons-Gomila; Julen Castellano; Julio Calleja-González; Javier Espasa-Labrador; Dimitrije Cabarkapa; Franc García (PLoS ONE, 2026)
Purpose The primary aim of the present study was to analyze the physical and physiological demands associated with different training tasks in women’s basketball. Methods Fourteen basketball players were continuously monitored for 22 weeks using WIMU PRO ® ™ local positioning system and GARMIN ® heart rate monitors. The variables examined included: distance (DIST in m), number of accelerations (>2 m·s -2 , HACC) and decelerations (<−2 m·s -2 , HDEC); high speed running (>18 km·h -1 , HSR in m), number of jumps (JUMPS), player load (PL in arbitrary units) and heart rate zones (>80% of maximum heart rate, HRZ in seconds). Training tasks were classified into three orientations: directed-oriented (DIR, drills without opposition), special-oriented (SPE, small-sided games), and competitive-oriented (COM, 4-on-4 and 5-on-5 formats); and further grouped by three levels of court space. The Shapiro–Wilk test was used to verify data normality. Linear mixed-effects models were used to analyze all variables. Skewed variables were log-transformed to meet model assumptions. Significance was set at p < 0.05. Results The SPE tasks showed higher values than COM tasks (p < 0.001) in all variables except for HRZ. Also, SPE tasks reported greater values than DIR in the following variables: HRZ and HSR (both p < 0.001) and PL (p = 0.008). Finally, DIR tasks showed higher values than COM tasks in DIST, HACC, HDEC and JUMPS (all p < 0.001), whereas COM tasks exhibited higher values than DIR tasks in HRZ (p < 0.001). Considering the court space in which the tasks were performed, differences were found in all the variables analyzed, with larger spaces generally resulting in greater demands in most variables. Conclusions The results describe that task orientation and court space influence the load demands in women’s basketball. DIR and SPE tasks elicited greater intensities than COM tasks, suggesting that training design should be strategically adapted according to the desired physical and physiological stimuli.